2006
DOI: 10.1200/jco.2005.02.9827
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy Is Associated With Decreased Survival in Women With Lung Cancer

Abstract: HRT may affect outcomes from lung cancer adversely. Further studies examining the role of HRT use on outcomes from lung cancer, especially in women with a history of smoking, are urgently needed to clarify this important problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 20 publications
4
115
0
8
Order By: Relevance
“…Unfortunately 58% of these patients will be diagnosed from developing countries (Brownson et al, 1992, Taioli 1994, Darby et al, 2001, Grupta et al, 2001, Lissowska et al, 2005, Darby et al, 2006, Ganti et al, 2006, Schrump et al, 2008, Ferlay et al, 2010, Bouchardy et al, 2011, Raùl Barrera-Rodriguez 2012. Although lung cancer is more frequent among men, it is a major threat to women today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately 58% of these patients will be diagnosed from developing countries (Brownson et al, 1992, Taioli 1994, Darby et al, 2001, Grupta et al, 2001, Lissowska et al, 2005, Darby et al, 2006, Ganti et al, 2006, Schrump et al, 2008, Ferlay et al, 2010, Bouchardy et al, 2011, Raùl Barrera-Rodriguez 2012. Although lung cancer is more frequent among men, it is a major threat to women today.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is the major risk factor for both genders. Other risk factors that can cause lung cancer among non smokers are passive smoking, radon, exposure to asbestos, occupational exposures, hormones and genetic factors (Brownson et al, 1992, Taioli 1994, Darby et al, 2001, Grupta et al, 2001, Lissowska et al, 2005 Ganti et al, 2006, Schrump et al, 2008, Ferlay et al, 2010, Bouchardy et al, 2011, Raùl Barrera-Rodriguez 2012. In this study, we present the clinical, pathological and survival datas of 50 female patients with lung cancer who were treated in our center.…”
Section: Introductionmentioning
confidence: 99%
“…Авторы установили также, что раннее (до 40 лет включительно) наступление менопаузы ассоциировано со снижением риска возникновения аденокарциномы легкого [19]. Результаты другого исследования подтвер-дили эти данные и показали, что гормонозаместительная терапия эстрогенами ухудшает показатели выживаемости у женщин, больных раком легкого [20].…”
Section: экспрессия эстрогеновых рецепторов в ткани немелкоклеточногоunclassified
“…Previous studies showed that a great majority of NSCLC expressed ERs (5 -8) and estrogen stimulated the growth of NSCLC tumors in nude mouse xenografts. In addition, hormone replacement therapy has been reported to significantly decrease survival in women with lung cancer (9). Therefore, estrogenic actions have been postulated to contribute to the development and/or progression of NSCLC.…”
mentioning
confidence: 99%